Sustainable assessment and carbon footprint analysis of polysaccharide biopolymer-amended soft soil as an alternate material to canal lining - Rasheed, Romana Mariyam; Moghal, Arif Ali Baig; Rambabu, Sathyanarayanan; Almajed, Abdullah (Frontiers in Environmental Science, 2023)
Kuttanad region in Kerala, India, is a place that predominantly consists of soft soil formations with low shear strength and low water resistance rendering them problematic for construction purposes. Pavements constructed on such soft deposits have been subjected to structural rutting and the high erodibility of the in-situ soil necessitates the need to employ suitable ground improvement techniques. The present environmental scenario demands the implementation of sustainable techniques for ground rejuvenation and effective stabilizers for enhancing engineering properties. This study investigates the amelioration of Kuttanad soft soil using chitosan as a soil amendment to improve its durability and erodibility characteristics. The untreated and chitosan-treated samples were exposed to 5 hours of wetting cycle followed by 43 hours of drying cycles until their failure. The unconfined compressive strength (UCS) of samples prepared with different dosages (0.5, 2, 4%) and cured for 14, 28, 60, and 90 days was evaluated at the onset and after each drying cycle to measure their durability index. Kuttanad soil was amended with 2% and cured for 90 days withstood five cycles with a UCS of more than 1000 kPa. The drip erosion tests were used to check the erodibility performance for the aforementioned different dosages and curing periods. The 2% and 4% chitosan amended samples resisted the entire test duration of 10 minutes indicating the highest water erosion resistance. The findings of the current study evaluated through durability and erosion tests reinforced the effectiveness of chitosan as an effective biopolymer for soft soils subjected to constant water attack and can be easily implemented in places with such vulnerability. A typical earthen canal lining amended with chitosan reduced the carbon emissions by 8.74 and 7.44 times compared to conventional amendments like lime and cement in Carbon Footprint Analysis.